EXPORT / IMPORT OF EDUCATIONAL MATERIALS IN ADAPTIVE DISTANCE LEARNING SYSTEM - Fedoruk, P.; Maslovsky, S.; Udud, O. (Journal of Information Technologies in Education (ITE), 2010)
The article deals with technological and methodological aspects of developing and implementing standards for import/export of material in adaptive systems learning and knowledge control (ASLKC). Applications developed standards allows the use of existing educational material for ASLKC of individualized education on the basis of adaptation to the level of knowledge of perception of information and other features of those enrolled. The implementation of research results created a crossplatform software module web interface design of electronic materials developed universal module interconversion major existing standards ASLKC (BLACKBOARD, RESPONDUS, SCORM, IMS, MOODLE GIFT).